Approximative Compactness and Radon-Nikodym Property in w∗ Nearly Dentable Banach Spaces and Applications. (6th May 2015) - Shang, Shaoqiang; Cui, Yunan
Abstract : Authors definew ∗ nearly dentable Banach space. Authors study Radon-Nikodym property, approximative compactness and continuity metric projector operator inw ∗ nearly dentable space. Moreover, authors obtain some examples ofw ∗ nearly dentable space in Orlicz function spaces. Finally, by the method of geometry of Banach spaces, authors give important applications ofw ∗ nearly dentability in generalized inverse theory of Banach space.